David Lean - A Life in Film - Wattis, Nigel (Network, 2012)
David Lean has the reputation as one of the world's great directors won by such films as "Doctor Zhivago", "The Bridge on the River Kwai" and "Lawrence of Arabia". After "Ryan's Daughter" (1970), he didn't make a film for 14 years. Now at age 76, he returns to the screen with "A Passage to India" (1985). This documentary traces the making of the film. [www.bfi.org.uk]